(untitled) (International scientific-electronic journal “Pioneering studies and theories”, 2025)
Encryption algorithms play a very important role in ensuring information security. Their main function is to protect data by changing it into an unreadable form (cipher). Encryption algorithms encrypt data in such a way that a person who does not have a key cannot read the information. This is especially necessary to protect important information, including personal, financial or commercial secrets. Encryption algorithms can also be used to ensure the integrity of the data. Cryptographic methods, such as Hash functions, allow the data to be checked for non-tampering. Encryption algorithms play an important role in ensuring the authentication of users or systems. Examples include password encryption, secure connection setup (SSL/TLS), and authentication via digital signatures.